Digital Literacy and Community Digital Cultural Adaptation: A Study of the Use of the Ferizy Application at Ulee Lheue–Balohan Port - Asyura Febriyandila; Taufik Taufik; Arif Ramdan Sulaeman (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2026)
This study is motivated by the transformation of ferry transportation services from a manual system to a digital platform through the Ferizy application, which has generated various responses and challenges among users. The main problem of this research lies in the intergenerational gap in digital cultural adaptation and the technical constraints that affect the effectiveness of application usage. This study aims to analyze the process of community digital cultural adaptation in using the Ferizy application for the Ulee Lheue–Balohan ferry service. The research employs a qualitative approach with a descriptive design. Data were collected through interviews with 15 informants selected purposively, consisting of different generational groups as well as port officers as supporting informants. The findings indicate that levels of knowledge, adaptation processes, and challenges in using the Ferizy application vary across generations. The younger generation tends to adapt more quickly to digital technology, while the older generation faces difficulties, particularly in digital literacy and the use of application-based systems. In addition, technical issues such as network disruptions and system errors also affect service effectiveness. The study implies that the success of digital service transformation depends not only on technological availability but also on social readiness and the level of digital literacy within the community. Therefore, improvements in digital education and infrastructure support are essential to ensure equitable access and optimal use of the service.